Identifying the Factors Contributing to the Volume of Coffee Export from North Sumatra to the United States, Malaysia and Japan - Fransisca Natalia Sihombing; Tavi Supriana; Sri Fajar Ayu (Universitas Sebelas Maret, 2021)
The fluctuation of coffee export from North Sumatra to the three primary destination countries, including the United States, Malaysia and Japan, has never been reported simultaneously. The research was aimed to analyze the factors affecting the volume of coffee export from North Sumatra to the United States, Malaysia and Japan. The research was conducted in November 2019 until March 2020. This study employed secondary data, which were obtained from the Statistics of Sumatera Utara, International Coffee Organization, Bank Indonesia and Trading Economics in the time series of 34 years (1986 until 2019). The data were analyzed using the quantitative descriptive method with the panel data regression analysis by applying the Chow and Hausman tests with the Eviews 10 software. The analysis results show that the Free on Board (FOB) value, Indonesia Coffee Prices (ICP), Rupiah Exchange Rate (RER), Gross Domestik Product (GDP) per capita and coffee yield simultaneously and significantly affected the Coffee Export Volume (CEV) from North Sumatra to the United States, Malaysia and Japan. The FOB value, ICP and coffee yield had a partially significant positive effect on the CEV from North Sumatra to the three countries. The GDP per capita had a partially significant negative effect, while the RER did not put significant effect on the CEV. The FOB value, ICP and coffee yield are necessary to be increased for maintaining and supporting a rise in the volume of coffee export from North Sumatra.